The education effect based on concept mapping on critical thinking skills of midwifery students - Zohreh Mirkazehi rigi (Babol University of Medical Sciences, 2020)
Background and objective: Enhancing critical thinking is a challenge faced in Medical profession. Evaluation of data and choosing proper intervention to reach a correct decision needs skillful thinking. . Midwife as a clinical decision maker uses critical thinking in providing proficient care. Present studies is aimed at determining the education effect based on concept mapping on critical thinking skills of midwifery students. Method: This quasi-experimental study with two groups design before and after training, was performed on 60 midwifery students in mashhad school of nursing and midwifery in 2016. The samples were selected by the convenience method and were randomly divided into two groups of based on concept mapping and routine group. Content was similarin both groups. Students of based on concept mapping  group were trained concept mapping and  for six hours during two week. Students of routine group were trained by lecture for six hours during two week. They were filled the Watson Glaser critical thinking test in the before and 1 month after study. Data was analyzed by SPSS software version 16 and descriptive statistical test, mann-whitney test, Wilcoxon test, friedman test. P< 0/05 was considered statistically significant. Results:  The results indicated that  one month after interventional, critical thinking skills was significantly increased in two groups (P<0/05) but this increased in based on critical thinking groupis It wasn't more than routine group. Conclusion: There is not much difference between the two groups after training and further studies should be done.